2019
DOI: 10.3390/molecules24203731
|View full text |Cite
|
Sign up to set email alerts
|

Chlojaponilactone B Attenuates Lipopolysaccharide-Induced Inflammatory Responses by Suppressing TLR4-Mediated ROS Generation and NF-κB Signaling Pathway

Abstract: The lindenane-type sesquiterpenoid chlojaponilactone B (1), isolated from Chloranthus japonicus, has been reported to possess anti-inflammatory properties. The present study aimed to further explore the molecular mechanisms underlying the anti-inflammatory activity of 1. RNA-seq analyses revealed the significant changes in the expression levels of genes related to multiple inflammatory pathways upon treatment of lipopolysaccharide (LPS)-induced RAW 264.7 murine macrophages with 1. Real time PCR (RT-PCR) and We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…3a and b, sesame significantly reduced expression of NF-κB1 by 50.7%, while rapeseed (73.9%) and casein (58.1%) down-regulated the expression of p65. Similarly, Ye et al (2019) and Gasparrini et al (2018) reported that chlojaponilactone B (2.5-10 μM) and manuka honey (8 mg/mL) attenuated LPS-induced increases in NF-κB1 and p65 gene expression, respectively. IκBα, functioning as an inhibitor of NF-κB transcriptional activation in the cytoplasm, prevents NF-κB activation and binding to the DNA (Jacobs & Harrison, 1998).…”
Section: Attenuation Of Nf-κb Activation In Lps-stimulated Raw 2647 M...mentioning
confidence: 84%
“…3a and b, sesame significantly reduced expression of NF-κB1 by 50.7%, while rapeseed (73.9%) and casein (58.1%) down-regulated the expression of p65. Similarly, Ye et al (2019) and Gasparrini et al (2018) reported that chlojaponilactone B (2.5-10 μM) and manuka honey (8 mg/mL) attenuated LPS-induced increases in NF-κB1 and p65 gene expression, respectively. IκBα, functioning as an inhibitor of NF-κB transcriptional activation in the cytoplasm, prevents NF-κB activation and binding to the DNA (Jacobs & Harrison, 1998).…”
Section: Attenuation Of Nf-κb Activation In Lps-stimulated Raw 2647 M...mentioning
confidence: 84%
“…Chlojaponilactone B was able to inhibit the expression 16 April 2020of NF-κB and pro-inflammatory mediators in LPS-induced RAW264.7 murine macrophage cell line by inhibition of toll like receptor 4 (TLR4) and myeloid differentiation factor 88 (MyD88) activation. Molecular docking studies showed that this compound bound to TLR4 in a similar manner to that of TAK-242, a TLR4 inhibitor [4].…”
mentioning
confidence: 84%
“…The D 4(5) double bond can be oxidized, forming the characteristic hydroxyl or peroxy-hydroxyl at C-4 or C-5 and migrating D 4(5) to D 5 (6) and D 15(4) (210)(211)(212)(213). Chlorahololides A (188), 151 C (189) 140 and spicachlorantin J (190) 152 possess a D 15 ′ (4 ′ ) double bond, and spicachlorantins E-F (191)(192), 153 sarcandrolide E (193), 107 chlorajaponilide E (194), 87 spicachlorantin G (195), 152,154 chlorasessilifol A (196), 155 fortunilides D-F (197)(198)(199), 49 chololactone B (200), 75 multistalide A (201), 141 chlomultiol B (202), 145 and sarcaglabrin B ( 203) feature an additional chiral center at C-4 ′ .…”
Section: Natural Product Reports Reviewmentioning
confidence: 99%
“…Chlojaponilactone B ( 65 ) could inhibit the nuclear translocation of NF-κB, the expression of iNOS, and the levels of inflammatory cytokines, thus improving the symptoms of ear swelling and the level of neutrophil infiltration, 209 and also blocked the activation of TLR4 and MyD88, thereby reducing ROS production. 210 Chloranthalactone B ( 83 ) inhibited the levels of NO, TNF-α, and IL-1β, and inhibited the phosphorylation levels of MAPK signaling pathway proteins by targeting MKK3/6. 207 LS dimer linderolides A–F showed NO production and cell growth inhibition activity.…”
Section: Biological Activitiesmentioning
confidence: 99%